Comparison of Histologic Characteristics of Chinese Chronic Hepatitis B Patients with Persistently Normal or Mildly Elevated ALT - Wang, Hong (Public Library of Science, 2013)
Liver disease can develop in chronic hepatitis B (CHB) patients with normal or mildly elevated alanine aminotransferase (ALT) who seldom undergo liver biopsy. We aimed to determine histologic characteristics of a large cohort of Chinese CHB patients undergoing liver biopsy and to evaluate the utility of ALT and HBV DNA values at the time of biopsy in predicting liver disease in this population. This prospective study enrolled 230 treatment-naïve patients with persistently normal or mildly elevated ALT. All patients had a liver biopsy. ALT, aspartate aminotransferase (AST), and HBV DNA levels were some of the other parameters measured. Using Scheuer's classification, significant histology was defined as stage ≧2 fibrosis and/or stage 1 fibrosis plus≧ grade 2 inflammation. Liver disease was observed in 34.4% and 61.8% of patients with normal ALT and mildly elevated ALT, respectively. Patients with mildly elevated ALT levels had significantly more events, including liver disease, elevated AST, and moderate to severe inflammation and liver fibrosis, than patients with normal ALT (all P≤0.005). A total of 107 patients (46.5%) had liver disease and 123 (53.5%) did not. PLT and ALT were significantly associated with liver disease (both P<0.001). Patients with elevated ALT, lower platelet count and HBV DNA < 7 log(10)copies/mL may have histologically significant changes associated with liver disease. Multivariate analysis showed that PLT and HBV DNA levels were significantly associated with liver disease in patients with normal ALT while gender and HBV DNA levels were significantly associated with liver disease in patients with mildly elevated ALT. Assessing liver damage via biopsy in patients with normal or mildly elevated ALT may help to identify those who would benefit from antiviral therapy.